Rediscovering Self with Tagore's Gitanjali (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The collection of poems by Rabindranath Tagore known as Gitanjali is arguably his most well-known work. In 1913, Tagore was awarded the Nobel Prize in Literature for this anthology. The collection of 103 poems began as a compilation of Bengali poetry in 1910. A few of the poems are even more personal; some are directed to God, while others are to a loved one on Earth. Without a doubt, poetry have highly uniform tones and meanings. whoever is addressed, reinforcing the firm conviction that love both human and eternal should be viewed equally. The majority of the poems are quite short and easily readable, making them suitable for almost anyone to read. When it comes to his creative career, he is well-known for his work in nearly all genres, including drama, stage plays, prose, novels, novellas, essays, and poetry. He thinks that developing a person's love for people will result in their spiritual change, and this can be accomplished by acquiring spiritual knowledge.